Does improved information improve incentives? - Chaigneau, Pierre; Edmans, Alex; Gottlieb, Daniel (Journal of Financial Economics, 2018)
This paper studies the value of more precise signals on agent performance in an optimal contracting model with endogenous effort. With limited liability, the agent’s wage is increasing in output only if output exceeds a threshold, else it is zero regardless of output. If the threshold is sufficiently high, the agent only beats it, and is rewarded for increasing output through greater effort, if there is a high noise realization. Thus, a fall in output volatility reduces effort incentives—information and effort are substitutes—offsetting the standard effect that improved information lowers the cost of compensation. We derive conditions relating the incentive effect to the underlying parameters of the agency problem.